Frontispiece: One‐Step Synthesis of 3, 4‐Disubstituted 2‐Oxazolidinones by Base‐Catalyzed CO2 Fixation and Aza‐Michael Addition. Issue 44 (5th August 2019) - Mannisto, Jere K.; Sahari, Aleksi; Lagerblom, Kalle; Niemi, Teemu; Nieger, Martin; Sztanó, Gábor; Repo, Timo
Abstract : 2‐Oxazolidinones are saturated heterocyclic compounds, which are highly desired structures in modern drug design. In their Communication on page 10284 ff., T. Repo et al. describe the use of CO2 as a carbonyl source for a new, single‐step approach to 3, 4‐disubstituted 2‐oxazolidinones. The modular reaction, which occurs between a γ‐brominated Michael acceptor, CO2 and an arylamine, aliphatic amine or phenylhydrazine, is catalyzed by 1, 1, 3, 3‐tetramethylguanidine (TMG). The method displays high yields (av. 75 %) and enables late‐stage functionalization of complex drug‐like molecules.